2020
DOI: 10.1002/ccr3.3365
|View full text |Cite
|
Sign up to set email alerts
|

A large asymptomatic portal vein aneurysm in an old man

Abstract: An 86-year-old Caucasian man was admitted to the emergency room (ER) for dyspnea. The patient's past medical history included ischemic heart disease with congestive heart failure, permanent atrial fibrillation on anticoagulant prophylaxis with warfarin, chronic obstructive pulmonary disease (COPD), and chronic kidney disease (stage IV K-DOQI) and was unremarkable for diseases affecting the digestive system. The patient also denied any surgical history, trauma, and malignancy. Routine laboratory tests including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Koc et al [ 11 ] reported an incidence of thrombophilia in 4 out of 7 patients with thrombosed PVA, hence, pointing on an importance of thrombophilic screening in all the subjects with diagnosed PVA, even if asymptomatic at the beginning. Even though 18 cases of non-thrombosed PVAs exceeding 5 cm in their largest diameter were reported in the literature, with no anticoagulation taken before their diagnosis, many authors support a thrombophilic risk assessment[ 12 ]. While all of our patients were asymptomatic, only one ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Koc et al [ 11 ] reported an incidence of thrombophilia in 4 out of 7 patients with thrombosed PVA, hence, pointing on an importance of thrombophilic screening in all the subjects with diagnosed PVA, even if asymptomatic at the beginning. Even though 18 cases of non-thrombosed PVAs exceeding 5 cm in their largest diameter were reported in the literature, with no anticoagulation taken before their diagnosis, many authors support a thrombophilic risk assessment[ 12 ]. While all of our patients were asymptomatic, only one ( i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Theories for a congenital cause involve inherent weakness in the vessel wall or incomplete regression of the distal right primitive vitelline vein, leading to a vascular diverticulum that ultimately develops into an aneurysm. Congenital PVAs are usually incidentally diagnosed later in life (not in neonatal or paediatric age groups) when an abdominal ultrasound is carried out because of some other indication[ 4 , 6 , 19 ]. Burdall et al [ 20 ] evaluated the relation between trisomy 21 (Down’s syndrome) and congenital vascular malformation of the liver in a study of 45 children, seven of whom had vascular malformation and two of whom had evidence of a PVA.…”
Section: Etiology Multimodal Imaging and Current Managementmentioning
confidence: 99%
“…With colour Doppler sonography of a PVA, anechoic areas will be completely filled, looking like the Korean flag or a “y in-yang ” sign. Hepatic artery aneurysms show a colour flow with arterial waveform, but choledochal cysts do not show such colour flow and are connected to biliary channels[ 6 , 15 ].…”
Section: Etiology Multimodal Imaging and Current Managementmentioning
confidence: 99%
“…However, the stability over time, the absence of any associated disease and the absence of clinically significant manifestations are considered to be arguments for the congenital type. The adaptation of the intrahepatic flow in congenital aneurysms allows a normal hepatic function without supplementary risk of complications whatever the patient's age, being described five cases in asymptomatic patients of 80-year-old and older [8]. Some cases presented in the literature developed symptoms correlated with the huge size of the PVA of up to 5-7 cm size, of probably congenital origin, such as encephalopathy [9], jaundice, or epigastric pain in an acute thrombose [10]; but almost ¾ cases, usually with small or moderate PVA, showed no symptoms related to its pathology [7].…”
Section: Introductionmentioning
confidence: 99%